Programación de abastecimiento y la gestión logística en la unidad de gestión educativa de Ucayali – Contamana 2022 - Reategui del Aguila, Guido Armando (2023)
The objective of the research was to determine the relationship between supply programming and logistics management in the Educational Management Unit of Ucayali - Contamana 2022, where an applied methodology and non-experimental design has been used; Consisting of a population and sample of 73 workers to whom a questionnaire was applied for data collection. After having processed the data in the Excel and SPSS V.26 program, the following results were obtained: the supply programming variable is qualified as regular (66%); For its part, the logistics management of the UGEL is regular (66%). Regarding the correlation, it is observed that there is a significant relationship between the variables, being contrasted by a coefficient and sig of (r=0.674, p=0.000); likewise for the determination of needs dimension (r=0.548; p=0.000); for consolidation of needs (r=0.703; p=0.000); in the same way the obtaining plan corroborated by (r=0.485; p=0.000); also execution of the programming of (r=0.596; p=0.000); and evaluation of the programming corroborated by a coefficient and a sig of (r=0.572; p=0.000), both dimensions are significantly related to the logistics management of the UGEL.